2023
DOI: 10.3389/fpls.2023.1204813
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming roadblocks for in vitro nurseries in plants: induction of meiosis

Abstract: Efforts to increase genetic gains in breeding programs of flowering plants depend on making genetic crosses. Time to flowering, which can take months to decades depending on the species, can be a limiting factor in such breeding programs. It has been proposed that the rate of genetic gain can be increased by reducing the time between generations by circumventing flowering through the in vitro induction of meiosis. In this review, we assess technologies and approaches that may offer a path towards meiosis induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…Many crops, when grown under natural conditions, are limited to only one to two generations per year. This includes the use of winter nurseries, which advance breeding by allowing annual crops to produce additional generations per year [ 12 ]. This results in the need for several years to develop new cultivars of crops.…”
Section: Optimization Of Growing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many crops, when grown under natural conditions, are limited to only one to two generations per year. This includes the use of winter nurseries, which advance breeding by allowing annual crops to produce additional generations per year [ 12 ]. This results in the need for several years to develop new cultivars of crops.…”
Section: Optimization Of Growing Conditionsmentioning
confidence: 99%
“…LED fixtures normally require less electric power. They also maximize photon capture efficiency, which is essential in increasing the plant growth rate, thereby increasing generation turnover in some plants [ 12 ] ( Figure 2 ).…”
Section: Optimization Of Growing Conditionsmentioning
confidence: 99%
“…These gametes can then be fused to make new genotypes. Meiotic underpinnings have been investigated in numerous studies in the past (reviewed by Cook et al., 2023 ), but factors leading to efficient in vitro meiosis induction in plants are yet to be identified. In a mammalian system, in vitro meiosis has been accomplished at rates around 1% ( Medrano et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies with plants have identified factors that reduce chromosomes to a haploid state in vitro in a meiosis-like fashion ( Yoshida and Yamaguchi, 1973 ; Chen et al., 2000 ; Yihua et al., 2001 ), however, the efficiency at which this is done is unknown ( Yan et al., 2017 ). Thus far, in vitro nurseries (IVN; De La Fuente et al., 2013 ; Cook et al., 2023 ) or cycling of gametes in vitro (COGIV; Murray et al., 2013 ), are only concepts. If we can learn how to trigger meiosis induction in vitro , we are closer to making these ideas a reality.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies with plants have identified factors that reduce chromosomes to a haploid state in vitro in a meiosis-like fashion (Yoshida and Yamaguchi, 1973;Chen et al, 2000;Yihua et al, 2001), however, the efficiency at which this is done is unknown (Yan et al, 2017). Thus far, in vitro nurseries (IVN;De La Fuente et al, 2013;Cook et al, 2023) or cycling of gametes in vitro (COGIV; Murray et al, 2013), are only concepts. If we can learn how to trigger meiosis induction in vitro, we are closer to making these ideas a reality.…”
mentioning
confidence: 99%